Pendampingan Kader Posyandu untuk Deteksi Dini Kanker Payudara melalui Pemeriksaan Payudara Sendiri - Pandawa, Rugaya M.; Saleh, Fatmah M. (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2024)
Breast and cervical cancer are the main types of cancer which are the largest contributors to all types of cancer in women. This community service aims to increase the knowledge of posyandu cadres in early detection of breast cancer. Posyandu cadre training is carried out for 8 hours per meeting and assistance for Posyandu cadres is carried out for 4 hours per meeting. A cadre of 10 people was prepared with the criteria for women of childbearing age who visited the posyandu after which they performed a breast phantom set. This research was conducted at the Salero Community Health Center in June 2023. The methods used included face-to-face lectures, questions and answers, and demonstrations with 10 posyandu cadres involved. The results of the research showed an increase in cadre knowledge, where before being given exposure to material and practice, only 10% of participants had sufficient knowledge, whereas after being given exposure to material and practice, good knowledge increased to 90%. The skill level of cadres was also very poor before being given exposure to material and practice where cadres with less knowledge reached 80%, and cadre skills increased after being given exposure to material and practice with cadres with good skills as much as 90%. Conclusion: The implication of the research is that cadre mentoring can be used as an appropriate method to increase cadres' knowledge and skills for breast self-examination.